Change in end-of-life care for Medicare beneficiaries: site of death, place of care, and health care transitions in 2000, 2005, and 2009 - Teno, Joan M; Gozalo, Pedro L; Bynum, Julie P W; Leland, Natalie E; Miller, Susan C; Morden, Nancy E; Scupp, Thomas; Goodman, David C; Mor, Vincent (JAMA : the journal of the American Medical Association, 2013)
A recent Centers for Disease Control and Prevention report found that more persons die at home. This has been cited as evidence that persons dying in the United States are using more supportive care. To describe changes in site of death, place of care, and health care transitions between 2000, 2005, and 2009. Retrospective cohort study of a random 20% sample of fee-for-service Medicare beneficiaries, aged 66 years and older, who died in 2000 (n = 270,202), 2005 (n = 291,819), or 2009 (n = 286,282). A multivariable regression model examined outcomes in 2000 and 2009 after adjustment for sociodemographic characteristics. Based on billing data, patients were classified as having a medical diagnosis of cancer, chronic obstructive pulmonary disease, or dementia in the last 180 days of life. Site of death, place of care, rates of health care transitions, and potentially burdensome transitions (eg, health care transitions in the last 3 days of life). Our random 20% sample included 848,303 fee-for-service Medicare decedents (mean age, 82.3 years; 57.9% female, 88.1% white). Comparing 2000, 2005, and 2009, the proportion of deaths in acute care hospitals decreased from 32.6% (95% CI, 32.4%-32.8%) to 26.9% (95% CI, 26.7%-27.1%) to 24.6% (95% CI, 24.5%-24.8%), respectively. However, intensive care unit (ICU) use in the last month of life increased from 24.3% (95% CI, 24.1%-24.5%) to 26.3% (95% CI, 26.1%-26.5%) to 29.2% (95% CI, 29.0%-29.3%). (Test of trend P value was <.001 for each variable.) Hospice use at the time of death increased from 21.6% (95% CI, 21.4%-21.7%) to 32.3% (95% CI, 32.1%-32.5%) to 42.2% (95% CI, 42.0%-42.4%), with 28.4% (95% CI, 27.9%-28.5%) using a hospice for 3 days or less in 2009. Of these late hospice referrals, 40.3% (95% CI, 39.7%-40.8%) were preceded by hospitalization with an ICU stay. The mean number of health care transitions in the last 90 days of life increased from 2.1 (interquartile range [IQR], 0-3.0) to 2.8 (IQR, 1.0-4.0) to 3.1 per decedent (IQR, 1.0-5.0). The percentage of patients experiencing transitions in the last 3 days of life increased from 10.3% (95% CI, 10.1%-10.4%) to 12.4% (95% CI, 12.3%-2.5%) to 14.2% (95% CI, 14.0%-14.3%). Among Medicare beneficiaries who died in 2009 and 2005 compared with 2000, a lower proportion died in an acute care hospital, although both ICU use and the rate of health care transitions increased in the last month of life.